2009
DOI: 10.1007/s10714-009-0821-y
|View full text |Cite
|
Sign up to set email alerts
|

LRS Bianchi type I models with anisotropic dark energy and constant deceleration parameter

Abstract: Locally rotationally symmetric Bianchi type I cosmological models are examined in the presence of dynamically anisotropic dark energy and perfect fluid. We assume that the dark energy (DE) is minimally interacting, has dynamical energy density, anisotropic equation of state parameter (EoS). The conservation of the energymomentum tensor of the DE is assumed to consist of two separately additive conserved parts. A special law is assumed for the deviation from isotropic EoS, which is consistent with the assumptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(100 citation statements)
references
References 55 publications
1
95
0
1
Order By: Relevance
“…Leon and Sarikadis (2010) have investigated that anisotropic geometries in modified gravitational frameworks present radically difference cosmological behaviors comparing to the simple isotropic scenarios. Akarsu et al (2010) In this paper, we have studied some physically realistic and totally anisotropic Bianchi-V models with anisotropic DE and perfect fluid. To study the anisotropic nature of DE, we have assumed the time dependent skewness parameter, which modify EoS.…”
Section: Introductionmentioning
confidence: 99%
“…Leon and Sarikadis (2010) have investigated that anisotropic geometries in modified gravitational frameworks present radically difference cosmological behaviors comparing to the simple isotropic scenarios. Akarsu et al (2010) In this paper, we have studied some physically realistic and totally anisotropic Bianchi-V models with anisotropic DE and perfect fluid. To study the anisotropic nature of DE, we have assumed the time dependent skewness parameter, which modify EoS.…”
Section: Introductionmentioning
confidence: 99%
“…For closed universe, the Hubble parameter , H the matter energy density parameter M  and the dark energy density parameter ,   predicted by Tegmark [12] by Sahni et al [23][24].This parameter ) ( t  have been calculated with some reasoning with reduced to some simple parameterization of the dependences by many authors [25][26][27][28][29][30]. The results from SNe Ia data collaborated with CMBR anisotropy and galaxy clustering statistics (Tegmark et al [12] [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 78%
“…Following, Akarsu and Kilinc [37,38,50] and Yadav [21], we split the conservation of energy momentum tensor of the DE into two parts, one corresponds to deviations of EoS parameter and other is the deviation-free part of T (de)ij ;j = 0:…”
Section: Solution Of the Field Equations And Its Physical Significancementioning
confidence: 99%
“…Setare [32][34] and Setare & Saridakis [35] have also studied the DE models in different contexts. Recently, dark energy models with variable EoS parameter have been studied by Ray et al [36], Akarsu and Kilinc [37,38], Yadav et al [39], Yadav and Yadav [40], Pradhan and Amirhashchi [41], Pradhan et al [42] and Amirhashchi et al [43,44]. In well-known reviews on modified gravity (Nojiri and Odintsov [45,46], it is clearly indicated that any modified gravity may be represented as effective fluid with time dependent ω.…”
Section: Introductionmentioning
confidence: 99%